Readmission following primary surgery for larynx and oropharynx cancer in the elderly. (23rd September 2016) - Chaudhary, Hamad; Stewart, C. Matthew; Webster, Kimberly; Herbert, Robert J.; Frick, Kevin D.; Eisele, David W.; Gourin, Christine G.
Abstract : Objective: To examine 30‐day readmission rates and associations with risk factors, survival, length of hospitalization, and costs in elderly patients with laryngeal and oropharyngeal squamous cell cancer (SCC). Study Design: Retrospective cross‐sectional analysis of Surveillance, Epidemiology, and End Results‐Medicare data. Methods: We evaluated 1, 518 patients diagnosed with laryngeal or oropharyngeal SCC from 2004 to 2007 who underwent primary surgery using cross‐tabulations, multivariate regression modeling, and survival analysis. Results: Thirty‐day readmission occurred in 14.1% of hospitalizations. Readmission was more likely in patients with postoperative complications during initial hospitalization (24.8% vs. 4.5%, P < 0.001), and was associated with an increased 30‐day mortality incidence rate (5.1% vs. 0.9%; P < 0.001). On multivariate analysis, 30‐day readmission was significantly associated with advanced stage (odds ratio [OR] = 1.81 [1.13–2.90]), comorbidity (OR = 2.69 [1.65–4.39]), divorced/separated marital status (OR = 2.00 [1.19–3.38]), preoperative tracheostomy (OR = 3.39 [1.55–7.44]), major surgical procedures (OR = 2.58 [1.68–3.97]), greater length of initial hospitalization (OR = 1.72 [1.09–2.71]), pneumonia (OR = 2.86 [1.28–6.40]), postoperative dysphagia (OR = 5.97 [2.48–15.83]), and cardiovascular events (OR = 5.84 [1.89–17.96]). Thirty‐day readmission was significantly associated with 30‐day mortality (OR = 5.89 [2.21–15.70) and higher 1‐year mortality (68.0% vs. 89.2%, P < 0.001). The mean incremental costs of surgical care were significantly greater for patients with unplanned readmission (15, 123 [10, 514–19, 732]), after controlling for all other variables. Conclusion: Unplanned readmissions are associated with increased short‐ and long‐term mortality and costs. Elderly patients with advanced disease, advanced comorbidity, lack of spousal support, pretreatment organ dysfunction, more extensive surgery, postoperative pneumonia, postoperative dysphagia, and prolonged hospitalization are at increased risk of 30‐day readmission. These findings suggest a need for targeted interventions before, during, and after hospitalization to reduce morbidity, mortality, and excess costs in this high‐risk population. Level of Evidence: 2c. Laryngoscope, 127:631–641, 2017